PENGARUH MODEL PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR SISWA KELAS VII DI SMP NEGERI 2 SATU ATAP KEPENUHAN HULU TAHUN PEMBELAJARAN 2014/2015 - Handayani, Sri; Lestari, Rena; -, Dahlia (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The purpose of this study is to find out the influence of Scramble learning model to the students. Study result of the creature variety at the seventh grade students. The type of this research is Experimental Quasi research. The design of this research is Nonequivalent Control Group Design. The collecting data technique is the students study result which are got sheets on the objective test item. Based on the result of analysis of the research data thitung score is higher than ttabel (4.44>1.99). In the other hand, Ha is accepted, it means there is influence of Scramble learning model to the students study result of the creatures variety material at the seventh grade students of SMP Negeri 2 Satu Atap Kepenuhan Hulu year academic 2014/2015.